STRATEGI GURU FIQIH MAWARIS DALAM MENANGGULANGI KESULITAN BELAJAR SANTRI DI PONDOK PESANTREN SYEKH IBRAHIM KUMPULAN - Ahmad Egil Sandi; Afrinaldi Afrinaldi; Salmiwati Salmiwati; Muhiddinur Kamal (KOLONI, 2022)
This research is based on the phenomenon experienced by students of class XI at the Islamic Boarding School Sheikh Ibrahim Group. Researchers saw at the research location the difficulties felt by students in learning Fiqh Mawaris caused by aspects of the educators who did not understand and had not mastered the science of Mawaris perfectly. In addition, teachers are also constrained by strategies and methods that are still monotonous and thus cause students not to understand the learning carried out by the teacher. Besides that, the factors of students are also the cause of Mawaris learning difficulties due to the low awareness of students about the importance of Mawaris science. The purpose of this study was to determine the form of Mawaris' learning difficulties felt by students and the efforts made by Mawaris's teacher to these problems. This study uses a descriptive type of research using a descriptive analysis approach to describe the conditions that occur based on information related to the Mawaris learning that occurred at the Sheikh Ibrahim Islamic Boarding School. The subjects of the research were 5 students of class XI and 1 teacher of Fiqh Mawaris. To collect data, the authors conducted interviews, observations and documentation. Then to ensure the validity of the data, the authors triangulate the data. Based on the results of the study, it shows that there are several factors that influence the learning difficulties of Mawaris experienced by students, namely: material factors and learning resources which include the many Mawaris terms, the determination of the distribution of Mawaris in the form of calculations and media sources which are only in the form of printed books, strategy factors and learning methods which include methods and strategies that do not vary as well as learning that is still teacher-centered, and time allocation factors which include the absence of a balance between material and learning time and the provision of learning that is only 1x meeting/week. The strategies/efforts made by the Mawaris Fiqh teacher include: Punishment (giving law), repeating lessons and applying the right method.  Keyword:  Learning Strategies, Learning Difficulties, and Mawaris Fiqh